2020
DOI: 10.3389/fpsyg.2020.585598
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Street-Dance Training on the Executive Function in Preschool Children

Abstract: Executive function is the center of cognitive function, emotional function, and social function, and plays an important role in children's cognitive development. Previous studies used music, sports, and other training methods to promote the development of children's executive function. but researchers are still exploring more comprehensive and effective training methods. Street-dance, as a comprehensive dance form integrating the characteristics of movement, music, rhythm, and so on, needs the coordination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 78 publications
3
41
0
1
Order By: Relevance
“…Working memory as measured by the Digit Recall score was also enhanced after the aerobic dance program but not for participants in the control group. These findings are in line with previous reports that creative dance training significantly influenced EF in children (Yetti et al, 2019) and with findings that a street dance program significantly improved cognitive flexibility, inhibition and working memory in preschool children (Shen et al, 2020). Oppici et al (2020) gave support in their finding that dance practice coupled with a high cognitive challenge improved working memory in children.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Working memory as measured by the Digit Recall score was also enhanced after the aerobic dance program but not for participants in the control group. These findings are in line with previous reports that creative dance training significantly influenced EF in children (Yetti et al, 2019) and with findings that a street dance program significantly improved cognitive flexibility, inhibition and working memory in preschool children (Shen et al, 2020). Oppici et al (2020) gave support in their finding that dance practice coupled with a high cognitive challenge improved working memory in children.…”
Section: Discussionsupporting
confidence: 93%
“…Moreno opined that short-term music training for 6 months significantly improved behavior and changed the growth of synapses, showing that music is a means of fostering brain plasticity (Moreno et al, 2009). As noted above, Shen et al (2020) also showed that street-dance training can improve children’s cognitive flexibility, and, similarly, Kosmat and Vranic (2017) found that elders with predispositions toward cognitive decline showed significantly better results in terms of their cognitive flexibility and their working memory after 10 weeks of classic dance, compared to elders who did not dance.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, with its social, physical, and creative components, dance appears as an ideal candidate to boost executive functions, and more specifically cognitive flexibility. Note that previous studies reported the effect of dance on cognitive flexibility in aging people (Coubard et al, 2011) and in pre-school children (Shen et al, 2020). This suggests that the effect of dance on cognitive flexibility is not limited to the current study's protocol and patients.…”
Section: Single-case Analysismentioning
confidence: 63%
“…A growing body of literature has demonstrated that EF can be enhanced throughout the lifespan, and in particular in pre-schoolers, with interventions and targeted training ( Zelazo, 2020 ; for a review, see Scionti et al, 2020 ). For example, studies have demonstrated that interventions that feature cognitive exercises (e.g., Röthlisberger et al, 2012 ), street dancing (e.g., Shen et al, 2020 ), or musical training (e.g., Moreno et al, 2011 ) effectively enhance EF in preschoolers. In a study with children 3–6 years of age, the authors tested the efficacy of an play intervention using wooden blocks ( Schmitt et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%